Artificial Circular RNA Sponges as a Novel Tool in Molecular Biology and Medicine - Breuer, Janina; Justus Liebig University Giessen (My University, 2022)
Within the recent years, circular RNAs (circRNAs) have aroused the interest of molecular biology, medicine and pharmaceutical science, due to their covalently closed structure and thus an elevated stability against exonucleolytic degradation compared to linear RNA molecules. Inspired by naturally occurring circRNAs functioning as sponges for cytoplasmic microRNAs (miRNAs), artificial circRNAs have been designed to not only specifically sequester but also functionally inhibit mature miRNAs related to human diseases like viral infections or cancer. The production of artificial circular RNA sponges (ciRS) displays a major limitation. To overcome this limitation, we promulgated a strategy for the efficient production and stringent purification of synthetic ciRS in a cell-free system, technically relying on enzyme-based in vitro transcription and RNA ligation. A former proof-of-principle study demonstrated the successful sequestration of the hepatocyte-specific miR-122 by engineered ciRS to impact the Hepatitis C virus (HCV) propagation. As part of this thesis, the oncogenic miR-21 was employed as a target for ciRS-based sequestration. Being the most abundant miRNA in human cancers, specific binding and functional inactivation of miR-21 by artificial ciRS not only impaired cancer cell proliferation and invasion in 3D tumor spheroids, but also inhibited tumor growth within a murine xenograft model system by de-repressing natural anti-proliferative miR-21 mRNA targets. Importantly, circularization of ciRS substantially increased the intracellular stability and therefore the availability of functional miR-21 binding sites as the half-lifes of artificial ciRS significantly exceeded those of their linear counterparts. Concerning the rapidly gained importance of RNA pharmaceuticals worldwide as well as the potential application of synthetic ciRS as powerful therapeutic strategy, one question remains to be answered: Would the therapeutic application of artificial ciRS trigger the cellular innate immune system? On that account, as part of this thesis, in vitro produced artificial ciRS previously used to inhibit miRNA functions and administered by lipofection were found to bypass cellular antiviral defense mechanisms. Contrarily, a circular construct encompassing extensive double-stranded sequence elements was found to potently induce intracellular signalling as chemokine-, interferon- and other innate immunity associated mRNA levels were up-regulated in a time- and dose-dependent manner comparable to commercially available immune-stimmulants. Immunoblotting revealed this highly double-stranded ciRS to trigger the activation of Protein Kinase R (PKR), an important RNA sensor in cellular immunity. In sum, ciRS produced with the presented methodology display a promising antisense tool to sequester disease-relevant miRNAs with cellular innate immune signalling pathways being bypassed depending on their sequence composition and secondary structure.
Keywords: circular RNA; circRNA; artificial circular RNA sponges; microRNA; ddc:500; ddc:570